The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ijc.28548
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the polarity protein PAR‐3 in clear cell renal cell carcinoma is associated with poor prognosis

Abstract: The partition-defective 3 (PAR-3) protein is implicated in the development and maintenance of cell polarity and is associated with proteins that mediate the changes in cytoskeleton organization required for cell polarity establishment. In this work, we used two original primary cell lines (R-180 and R-305) derived from clear cell Renal Cell Carcinoma (ccRCC) surgical specimens of a patient with unfavorable clinical course (R-180 cells) and a patient with favorable prognosis (R-305 cells) to identify genetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Genome-wide screening for microdeletions revealed that the region containing the Par3 gene ( PARD3 ) is deleted in lung, head and neck, and esophageal squamous cell carcinoma cell lines [29, 30]. In breast, esophageal, and lung cancers, Par3 seems to act as a tumor suppressor [22, 23, 25], whilst in clear-cell renal carcinoma, Par3 overexpression is associated with poor prognosis [27, 28]. In skin cancer, Par3 may act as a tumor suppressor or tumor promoter depending on the tumor type [24].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide screening for microdeletions revealed that the region containing the Par3 gene ( PARD3 ) is deleted in lung, head and neck, and esophageal squamous cell carcinoma cell lines [29, 30]. In breast, esophageal, and lung cancers, Par3 seems to act as a tumor suppressor [22, 23, 25], whilst in clear-cell renal carcinoma, Par3 overexpression is associated with poor prognosis [27, 28]. In skin cancer, Par3 may act as a tumor suppressor or tumor promoter depending on the tumor type [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found a significant 1 Mb gene amplification of the 10p11.21 locus encompassing the partition-defective 3 gene (PARD3), in addition to its protein overexpression (PAR-3), in a cell line derived from a ccRCC tumor of worse clinical outcome [13]. PAR-3, belongs to a partition defective complex that controls polarity, which is mainly composed of PAR-3, PAR-6 and atypical protein kinase (aPKC) [14].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] However, in some other tumors, such as liver cancer, ovarian cancer, and renal clear cell carcinoma, PAR3 overexpression supports cancer cell proliferation and is associated with poor cancer prognosis. [8][9][10][11] All these evidences implicated the complex regulatory network of cell polarity and its interaction with oncogenic and tumor suppressor pathways. Recently, PAR3L has been identified as a new member of polarity protein family and exhibits pro-oncogenic activity by maintaining cell stemness and disrupting cell tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] We then used Kaplan-Meier analysis to investigate the association of its homolog PAR3L with the survival of CRC patients. As shown in Figure 2(a), CRC patients with positive PAR3L expression had significantly lower survival rate than those with negative PAR3L tumors (log-rank test: p = 0.047).…”
Section: Par3l Overexpression Is Predictive Of Poor Crc Prognosismentioning
confidence: 99%
See 1 more Smart Citation